TANGGUNG JAWAB PELAKU USAHA ATAS KESESUAIAN JASA DENGAN IKLAN (STUDI KASUS KHAISAR WEDDING BATURAJA DAN KONSUMEN SILVA JUNISTIA): Business Actors’ Responsibility for Service Conformity with Advertisements (Case Study of Khaisar Wedding Baturaja and Consumer Silva Junistia) - Nasya Nadya; Halim, Suci Lestari (Faculty of Law, Universitas Trisakti, 2026)
Khaisar Wedding Baturaja provided services on the wedding day that did not match the advertisements on instagram or the agreement made with the consumer, Silva Junistia. This article examines the responsibility of Khaisar Wedding Baturaja for the discrepancy between the services provided on the wedding day and the representations in instagram advertisements and/or the agreement. The research method used is normative and descriptive, utilizing secondary data supported by interviews. Data were collected through a literature review, analyzed qualitatively, and conclusions were drawn using the deductive method. The results show that Khaisar Wedding Baturaja’s responsibility was limited to an apology without providing compensation, which is not in accordance with Article 19 paragraph (1) of the Consumer Protection Law (UUPK). In addition, the Instagram advertisements violate the Indonesian Advertising Ethics Guidelines. If the business operator does not provide compensation, the consumer may pursue legal remedies by filing a lawsuit through the Consumer Dispute Settlement Agency or the District Court at the consumer’s place of residence pursuant to Article 23 of the UUPK and Article 1243 of the Civil Code.